Mechanical reinforcement and memory effect of strain-induced soft segment crystals in thermoplastic polyurethane-urea elastomers. (3rd May 2021) - Candau, Nicolas; Stoclet, Gregory; Tahon, Jean-François; Demongeot, Adrien; Yilgor, Emel; Yilgor, Iskender; Menceloglu, Yusuf Z.; Oguz, Oguzhan
Abstract: An amorphous poly(urethane-urea) copolymer composed of 70 wt% poly(ethylene oxide) (PEO) soft segments (SS) (Mw  = 2000 g mol −1 ) and 30 wt% cycloaliphatic hard segments (HS) was subjected to in-situ X-Rays during tensile deformation. Mechanical hardening at room temperature was attributed to strain induced crystallization (SIC) of the PEO SS through the multiplication of aligned crystallites. The permanent nature of these crystals after stress removal indicates a certain mechanical stability, which we related here to the concomitant effect of superstraining of the SS crystallites and the HS reorganization upon deformation. This is in marked contrast to previous studies which reported the crystalline phase to be temporary upon unloading. A manifestation of such enhanced stability is the memory effect evidenced by an increased crystallizability of PEO segments during incremental cyclic loading. These results offer a way to ( i ) tune the mechanical properties of TPUs via the formation of mechanically stable pre-oriented SS crystals and to ( ii ) tune the thermally/water activated shape memory properties of TPUs (shape fixity, kinetics of shape memory recovery). Graphical abstract: Image 1 Highlights: Mechanical hardening in TPU due to strain induced crystallization (SIC) of PEO SS. SIC is found permanent after stress removal for sufficiently applied load. The SS crystals keep the memory of their strain induced orientation. Improved mechanical performance of pre-stretched TPU containing PEO crystals.